2 Years follow up Sex Reassignment Surgery: Mental Health and its Associated Factors - Jalilvand, Maryam; Bastani, Barbod; Emamhadi, MohammadAli (Archives of Men’s Health, 2020)
Introduction: Transsexualism is a gender disorder in which the patient’s physical gender is in conflict with his / her mental gender and emotionally and psychologically feels that he / she belongs to the opposite sex. There are several ways to correct this disorder and improve a person’s physical and mental health. Gender reassignment surgery is one of the treatment methods commonly performed for this purpose. Materials and Methods: This cross-sectional study was performed in 2019 in patients referred to the psychiatric ward of the Forensic Medicine Organization, Dr. Mir Jalali Surgery Center and the Welfare Organization. The sample size was 30 people according to the facilities of the research team, which was selected by census sampling method. After completing the informed consent to participate in this research project, all subjects completed the GHQ-28 mental health questionnaire and the researcher-made information form. Subsequently, the results were statistically analysed under SPSS21 statistical software.Results: Amongst the 30 participants (Male to Female /Female to Male = 14/16), the mean age was 27.06 ± 2.40 years, the mean time after surgery was 30.17 ± 3.18 month and the mean age of sexual identity change was 10.45 ± 3.91 year, respectively. Illicit drugs were used by 20% of these people, all of whom were amphetamines. The majority of the samples were dissatisfied with family and community support. Also, no difference was reported in the quantity and quality of intercourse before versus after surgery. The results of GHQ-28 mental health questionnaire showed that all items were lower than the community average. There was no significant difference in mental health between the two groups. Conclusion: Financial and spiritual support of family and society is very effective on Gender reassignment surgery results, especial sexual function. It seems that despite the significant advancements made in the field of sex reassignment, such operations and the resultant change in individuals’ gender have not met their needs.